Reception of Islamic Law On Indigenous Communities: - Prawiro, Abdurrahman Misno Bambang (Kawalu: Journal of Local Culture, 2015)
The first community to accept Islam was the tenant at the coastal areas of Sumatra, Java, Sulawesi, Kalimantan, Maluku, Nusa Tenggara and Papua. After that Islam disseminated to rural areas throughout the country as the consequence of their reception of Islamic law. However, the fact was not all Islamic law accepted and implemented, because they already have customs practiced continuously by hereditary generations long before the arrival of Islam. Some custom in Indonesia, which still survive was practiced by indigenous community such as Baduy and Kampung Naga. This research examines the reception of Islamic law by those indigenous communities. The focus of this study is the elements of Islamic law, the reception pattern of Islamic law, and the factors that influence the reception. The purpose and usefulness of this study was to answer the research questions and describe the two customary of communities as well as bad correlation with the Islamic legal system. The method used is empirical legal study. The data used in this study were the primary data source derived from observation, deep interviews and library research. Research shows that the reception of Islamic law by the community of Baduy in the implementation of Islamic law marriage that is reading the creed of the Prophet Muhammad PBUH records by KUA, especially on the community of Outer Baduy. Reception  in the field of inheritance was limited to the mention of the terms in Islamic inheritance, while the division still follow their customs that divide the estate equally both boys and girls. While the community of Kampung Naga reception occurs in the majority of law and worship in particular muamalah especially in wedding. Islamic law reception process occurs due to internal factors (custom character and creed) and external (social interaction and the power of the state).The researcher formulated the theory of Islamic law reception by the indigenous communities is Reception through Selection-modification, reception of Islamic law by indigenous communities with the selection and  modification. If Islamic law  is in accordance with the accepted custom, when it conflicts then modified to align with traditional values.Keywords: Reception of Law, Legal Anthropology, Indigenous Community, Adat, Islamic Law, Baduy, Kampung Naga and Theory Reception through Selection-modification.